As TDICs na EJA: contribuições em teses e dissertações da CAPES - Gonçalves, Letícia Fernanda (Universidade Federal de São Carlos, 2021)
This investigation had as its central theme the Information and Communication Technologies and Mobile Technologies at EJA: Contribution to Capes theses and dissertations. As a research question, we proposed to investigate: how technologies relate to Youth and Adult Education, specifically in terms I and II, in Capes Theses and Dissertations? Methodologically, we conducted a literature search and identified theses and dissertations defended from 2010 to 2019 that researched on the topic. The descriptors used in the search were: “youth and adult education” and “technologies”. After reading the titles, keywords and abstracts presented, the data were grouped using the proposed analysis of meanings present in the speech, the meaning cores, according to Aguiar and Ozella (2013). As meaning cores, we had: teacher training in technologies at EJA; EJA and its subjects; and the school as the main formative agent in the subjects' lives. The results allowed the realization of some considerations, such as: the importance of continuing education, the lack of public policies that support EJA, as well as research in this type of teaching.
The TDICs at EJA: contributions to CAPES thesis and dissertations
Keywords: Educação de jovens e adultos; Tecnologias; Alfabetização; Youth and Adult Education; Technologies; Literacy; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM